2005
DOI: 10.5688/aj690590
|View full text |Cite
|
Sign up to set email alerts
|

The “Research Track” Concentration, a New PharmD Elective Option

Abstract: Objectives. To enhance student curricular satisfaction, position students for multiple career options, and counter the national deficit in pharmacy faculty members by creating a research elective for students enrolled in a first-professional degree PharmD program. Design. The research track consists of 12 credit hours of didactic, seminar, and research courses. This concentration option entails graduate-level coursework and 2 consecutive semesters of attending a graduate seminar course and conducting independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Students completing research projects that required data collection and analysis (n 5 12) were commonly allowed to collect data from chart reviews (11), surveys (11), databases (11), interviews (10), clinical measures (10), laboratory procedures (9), and direct observation (8). Half (6) of the 12 colleges allowed students to use systematic reviews (eg, meta-analysis).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students completing research projects that required data collection and analysis (n 5 12) were commonly allowed to collect data from chart reviews (11), surveys (11), databases (11), interviews (10), clinical measures (10), laboratory procedures (9), and direct observation (8). Half (6) of the 12 colleges allowed students to use systematic reviews (eg, meta-analysis).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is a need to at least introduce research to students in professional programs. The introduction could range from requiring all students to conduct a full research project, to providing elective research opportunities, 6,7 to developing research tracks within the PharmD program, 8 to participating in the research of faculty members. The Accreditation Council on Pharmaceutical Education (ACPE) accreditation standards for the doctor of pharmacy degree address the need for graduates to understand research processes and identify the need for coursework in biostatistics, drug information, literature evaluation, and research design.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Attempts to enhance students' skills and depth of knowledge by offering focused concentrations also have been described in the literature. [7][8][9][10] The Southern Illinois University Edwardsville (SIUE) School of Pharmacy has developed an education concentration for PharmD students to address faculty recruitment and retention. The concentration requires that more than 50% of a student's didactic electives, ie, 6 or more of the 11 didactic elective credits and 1 advanced pharmacy practice experience (APPE) focus on a specialized track.…”
Section: Introductionmentioning
confidence: 99%
“…Key topics were defined according to reported findings and elective research rotation supportive rationale as previously reported. [4][5][6][7][8][9][10] Thirty-five topics were chosen and each topic was sequentially numbered in order to provide differentiation. The investigators were able to obtain 15 reflections from six of the 12 student pharmacists from the Experiential Education office of the college.…”
Section: Data Collection and Evaluationmentioning
confidence: 99%